Imposition of good Samaritan laws to improve professionalism among medical practitioners - Ashraf, Aishath Iffa; Faiz, Najy; Ariffin, Adlina (IIUM Press, International Islamic University Malaysia, 2017)
This paper discusses a legal-moral conflict that exists in the medical field which pertains to the duties of medical practitioners toward their patients. More specifically, it deliberates on paradoxical situations where medical practitioners are ‘legally permitted’ to refuse rendering their services to those in need due to the principles entrenched in the law of negligence. This legal conundrum has created a moral ‘neglect’ on the part of the medical practitioners toward their patients. Hence, this paper argues that the concepts inherent in the Good Samaritan laws should instead be imposed on medical practitioners in Malaysia, particularly, since neglecting patients who are in need of medical attention transgresses the Islamic principle of helping ones neighbours and the needy, contravenes the Hippocratic Oath and infringes the conscience of a morally upright individual.